2018
DOI: 10.7150/jca.26497
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 involves in breast cancer metastasizing to the spine via the Src/FAK signaling pathway

Abstract: C-X3-C chemokine ligand 1 (CX3CL1) has been shown to be involved in the development of multiple tumors. Our previous study demonstrated that CX3CL1 may be involved in the process of metastasis of various malignant tumors to the spine, including breast cancer, but the molecular mechanism was still unknown. In the present study, we found that the receptor CX3CR1 was overexpressed in the spinal metastases of breast cancer than in para-tumor tissue. In terms of CX3CL1, it was significantly more expressed in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 34 publications
5
50
0
Order By: Relevance
“…High levels of CX3CL1 in cells can attract those cancer cells expressing its receptor CX3CR1 and trigger them to invade the tissue and form metastases as seen e.g. in breast cancer spinal metastases [49]. In our study, we showed that CX3CL1 is selectively elevated in the serum of breast cancer patients with cerebral metastases.…”
Section: Patient Serum and Recombinant Chemokines Lead To Reduced Barsupporting
confidence: 58%
“…High levels of CX3CL1 in cells can attract those cancer cells expressing its receptor CX3CR1 and trigger them to invade the tissue and form metastases as seen e.g. in breast cancer spinal metastases [49]. In our study, we showed that CX3CL1 is selectively elevated in the serum of breast cancer patients with cerebral metastases.…”
Section: Patient Serum and Recombinant Chemokines Lead To Reduced Barsupporting
confidence: 58%
“…At the sites of cell-substratum focal adhesions, FAK can combine withSrc to form a dual-kinase complex [20], which coordinate cell behavior through regulating downstream pathways and molecules, including AKT, p38 and ERK kinase [21,22]. Autophosphorylation of Src/FAK complexes is a critical event in cancer progression and metastasis [23]. Src/FAK pathway kinases in solid tumors have been viewed as an attractive target in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The escaping of circulating tumor cells from the micro-vasculature of primary sites and extravasating into distant sites are the most important steps of the metastatic cascade. Our previous study showed that the vertebral marrow sinusoids were full of CX3CL1, which plays an important role in the process of spine metastases derived from CX3CR1-expressing cancer cells (Liang et al, 2018;Liu et al, 2018). During the above process, CX3CL1 chemo-attracted tumor cells and functioned as an adhesion molecule to arrest circulating cancer cells in the vertebra (Fong et al, 1998;Yao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Src is one of the most widely studied members of the SFKs. Our previous studies found that CX3CL1 quickly activated Src signaling in several tumor cells (Liang et al, 2018;Liu et al, 2018). Interestingly, another study reported that Src regulated cytoskeleton remodeling in Schwann cell morphology and motility (Melfi et al, 2017).…”
Section: Introductionmentioning
confidence: 95%